Non-Uremic Calciphylaxis: a Rare Diagnosis with Limited Therapeutic Strategies - Gomes, F (2022)
Calciphylaxis is a rare condition characterized by the emergence of non-healing skin ulcers secondary to arterial calcification and thrombosis, typically diagnosed in patients with end-stage kidney disease (ESKD). When it develops in patients without ESKD, it is called non-uremic calciphylaxis (NUC). The latter is an even rarer diagnosis with an uncertain pathophysiology and a high mortality rate (52%), mainly due to sepsis (50%). Cutaneous biopsy is diagnostic. Therapeutic measures recommended for NUC are limited to wound debridement, analgesia, and control of infection and risk factors. Other therapeutic options exist but with a low level of evidence. We present the case of a 78-year-old woman with NUC in her lower limbs who died of sepsis. NUC is a therapeutic challenge lacking efficient strategies. Learning points: Calciphylaxis in the absence of end-stage kidney disease is called non-uremic calciphylaxis (NUC).This disease is a diagnostic and therapeutic challenge.As therapeutic strategies for NUC mainly derive from those for uremic calciphylaxis, more efficient therapeutic measures and evidence-based recommendations are needed.